Effects of commonly used chronic medications on the outcomes of ipilimumab therapy in patients with metastatic melanoma. Issue 6 (December 2016) - Failing, Jarrett J.; Finnes, Heidi D.; Kottschade, Lisa A.; Allred, Jacob B.; Markovic, Svetomir N.
Abstract : Ipilimumab can induce long-term survival in 20% of patients with metastatic melanoma. Concurrent chronic medications may impact the patient's immune system, possess antimelanoma properties, and potentially affect clinical outcomes. This retrospective study sought to describe the efficacy and toxicity effects of 12 classes of chronic medications in metastatic melanoma patients treated with ipilimumab. A total of 159 adults who received ipilimumab for metastatic melanoma at Mayo Clinic (Rochester, Minnesota, USA) from 1 March 2011 through 31 December 2014 were included. Classes of chronic medications included statins, metformin, β-blockers, angiotensin-converting enzyme inhibitors/angiotensin-receptor blockers, calcium channel blockers, aspirin, non-steroidal anti-inflammatory drugs, H1 and H2 receptor antagonists, proton pump inhibitors (PPIs), antidepressants, and vitamin D supplements. Of the 12 medication classes, only PPIs were found to have an increased odds of experiencing a partial response or a complete response to ipilimumab [odds ratio: 3.73; confidence interval (CI): 1.26–11.04; P =0.02] on the basis of a case–control analysis. Although not significant, PPI use also trended toward improved overall survival and progression-free survival (hazard ratio: 0.44; CI: 0.17–1.15; P =0.09; and hazard ratio: 0.6; CI: 0.34–1.06; P =0.08, respectively) on the basis of Kaplan–Meier and Cox proportional hazard modeling. No medication class was associated with an increased risk of grades 3–5 immune-related adverse events with ipilimumab on the basis of case–control analysis. In summary, patients on PPIs may be more likely to experience a partial response/complete response following ipilimumab therapy. Because of the small sample size and the retrospective nature of this work, these findings are only descriptive and further study should be carried out. Other classes of chronic medications did not produce statistically significant effects for any of the measured outcomes.